Hydrological Modeling of Jamtara Watershed, Jharkhand of the Ajay River Catchment, through Soil Moisture Accounting Parameters - Sujana Dhar; Asis Mazumdar (Journal of Soil and Water Conservation, 2022)
A very exhaustive study was conducted on the Jamtara watershed, West Bengal of the Ajay river catchment under changed climate scenario from soil moisture accounting parameters. An attempt has been made to quantify the impact of climate change on the water resources of the Ajay river catchment outlet at Jamtara, using a distributed hydrological model HEC - HMS after due calibration using historical data and GIS coupled with RS. The study uses the Hadley Regional Model daily weather data to determine the control (present) and GHG Green House Gas (future climate scenario) water availability in space and time. A total of 15 years of simulation spanning the entire Ajay river catchment has been conducted. Five years were devoted to control (present) 1 997 - 2001 and the remaining 10 years (2040 - 2050) devoted to GHG (future) climate scenario. Seasonal shift of stream flow pattern, reduction of peak flow and water stressed condition have been observed.